Resource mobilization for sustainable management: proceedings of a Workshop on Major Irrigation Schemes in Sri Lanka, Kandy, Sri Lanka, 22-24 February 1990 - International Irrigation Management Institute (International Irrigation Management Institute, 1990)
Papers focus on institutional reform that is seen as a prerequisite to effective mobilization of sufficient resources for sustainable management of major irrigation schemes. They analyze the impediments to high performance system management within the irrigation management agencies and the direction in which reforms must go to bring improvements and identify broader policy issues and recommendations that are very important to the whole change process underway.